Perancangan Sistem Informasi Bank Darah Menggunakan Basis Data NoSQL - Rian Fatoni Tri Wicaksono; Erna Kumalasari Nurnawati; Renna Yanwastika Ariyana (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2022)
The existence of a blood exchange transaction process through a system carried out by the community, causing storing and managing data on a large scale is now causing problems in terms of scalability for blood bank managers in Yogyakarta. The process of blood transactions carried out by PMI units and hospitals at any time, makes the structure of relations in the blood banking system more complicated. In fact, every PMI unit and hospital in Yogyakarta requires a real-time data collection and storage process, considering that access to mobility of blood transactions is carried out almost 24 hours a day. Implementing an information system using a non-relational database model, is an alternative in the process of simplifying the relational structure in data relationships, this is because the non-relational database uses a NoSQL database model that provides support for database speed so that it remains optimal. In the research conducted, an information system was created that applied a non-relational database model to a case study of a blood bank information system. Where the NoSQL database is suitable for blood bank systems because it has high performance and is non-relational with real-time data storage and retrieval processes. The research conducted resulted in a blood bank information system that was developed using the Firebase database, where this system can display some data from the database such as viewing blood stocks, hospitals, blood donor events, and other information that is carried out in real time.